Typology of Access to Land Resources and Socio-Ecological Dynamics in the Coastal Community of Pasaran Island, Lampung Province, Indonesia - Jessica Vanelia Amanda; Arya Hadi Dharmawan; Soeryo Adiwibowo (Jurnal AGRISEP, 2025)
Differences in land access on Pasaran Island reflect complex inequalities between local and migrant groups, and between communities with different economic power. The social-ecological dynamics involved control of land resources and reclamation. The absence of appropriate regulations has led to tensions. Using a qualitative method using in-depth interviews with 14 informants. Informant selection based on purposive sampling technique based on criteria, primary data was collected from 14 informants who were directly involved in the social-ecological dynamics created on Pasaran Island, including the Local Government (Marine and Fisheries Office of Bandar Lampung City and Land Office of Bandar Lampung City), Head of Village, Head of Neighborhood Association, Local Community (Bugis), Migrant Community (Cirebon and Indramayu), and Community Leaders.  Data collection was closed after data saturation was reached when no more new information emerged, and the data collected as a whole formed a complete story. This research explores issues of access struggle and social-ecological dynamics within the framework of access theory. Based on understanding these land access and socio-ecological dynamics, the government can take more appropriate steps to manage resources, prevent conflict, and support environmental sustainability and community welfare on Pasaran Island.